METAKAOLIN BASED GEOPOLYMER CONCRETE MIX DESIGN SUITABLE FOR REINFORCED CONCRETE USE - Aliyu, I.; Kaura, J. M.; Abubakar, I.; Ocholi, A. (FUDMA JOURNAL OF SCIENCES, 2023)
Geopolymer concrete (GPC) has no mix design code to guide in the choice of material proportions for specific compressive strengths, its properties have not been fully understood especially in Nigeria despite being blessed with abundant geopolymer Al-Si source material (Kaolin). This study presents the properties of Kankara kaolin before and after treatment. Minitab 18 factorial design was used to design a Metakaolin based Geopolymer Concrete (GPC) with target compressive strength of 25 N/mm2 (Suitable for Reinforced concrete). After kaolin treatment XRF results indicate a marginal difference in Oxide composition with the kaolin before treatment, but FTIR results showed more of the difference because the transmittance of the band between 3619 and 3690 cm-1 which is typical of kaolin increased when treated to 94.484 % from 74.825 % when untreated and quartz interference at 1114.5 cm-1 and Si-O quartz at 674.6 and 752.9 cm-1 were no more after the treatment. A factorial design with four factors having 9 experimental runs recoded 39.5 N/mm2 (Run No 7) as highest compressive strength and 4.1 N/ mm2 (Run No 2) as the lowest. Results indicated that mixes with low alkaline liquid and low Molar concentration content exhibits lower strength than those with high alkaline liquid content and High Molar concentration. Re-analysing laboratory results and targeting a strength of 25 N/mm2; a mix (M1) with 14M proposed for the validation attained 38.7 N/mm2, another mix (M2) with 8 M also attained 30 N/mm2, Both M1 and M2 are satisfactory going by ACI 211.4R.93 1998